2017
DOI: 10.1520/jte20160451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unit Weight on Porosity and Consolidation Characteristics of Expansive Clays

Abstract: This study investigated the relationship between pore characteristics and unit weight of clayey soils. This relationship was particularly important in case of expansive soils, as the pore characteristics determine moisture flux boundaries, which in turn represent volume change behavior. Current research tried to evaluate the effect of compaction unit weight on the pore size and pore volume along with consolidation and swell characteristics on two expansive clays from semi-arid environment. The two selected cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…M. Kotilek summarized 12 kinds of NON-Darcy V-I relations and believed that the experimental method and errors in the experimental process were the main reasons for the deviation of the seepage law from Darcy's law. Zhang Zhong explained the deviation phenomenon from the perspective of bound water and believed that the non-Darcy seepage in clay was due to the non-Newtonian behavior of pore water [ 7 ]. L. Erge believed that whether Darcy's law applies to clay should be further discussed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. Kotilek summarized 12 kinds of NON-Darcy V-I relations and believed that the experimental method and errors in the experimental process were the main reasons for the deviation of the seepage law from Darcy's law. Zhang Zhong explained the deviation phenomenon from the perspective of bound water and believed that the non-Darcy seepage in clay was due to the non-Newtonian behavior of pore water [ 7 ]. L. Erge believed that whether Darcy's law applies to clay should be further discussed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chittoori et al tested the effect of porosity, consolidation, and the unit weight of expansive clays. Their study was important in the wake of soil treatment with microbes because pore size and size of pore throat play important roles in microbial treatment [118]. Figure 4 shows the maximum reduction of permeability in percentage achieved by different researchers in their studies after the biomineralization of soils.…”
Section: Reduction Of Hydraulic Conductivity By Biotreatmentmentioning
confidence: 99%
“…There are very few studies that explored the application of MICP in expansive soils. To test the hypothesis that the low pore space in these soils is not compatible for MICP application, Chittoori et al [27] performed a mercury intrusion porosimetry (MIP) study on two expansive soils to observe the pore size and pore volume at different compaction levels. It was found that 30% to 50% of the pore volume was larger than 1.5 µm (the average cell size of typical urease-producing soil bacteria) at the MDUW [27].…”
Section: Applications Of Micpmentioning
confidence: 99%
“…The presence of urea works as a nitrogen source, and the increase in the pH level as a result of the presence of ammonium from urea hydrolysis creates an environment for bacteria that can survive in a high-pH environment and use urea or ammonia as a nitrogen source [14]. As the number of ureolytic bacteria increases, the rate of hydrolysis increases, which increases the rate of precipitation [27].…”
Section: Treatment Solutionsmentioning
confidence: 99%
See 1 more Smart Citation